Experimental research on the effect caused by effective stress change in injection production capacity of carbonate reservoir - Gao, Xinping; Yang, Jian; Han, Huifen; Peng, Junliang; Peng, Huan; Yang, Zhifan (Frontiers in Earth Science, 2023)
The effective stress of the reservoir rock in the gas storage changes with the multi cycle injection and production, which changes the physical characteristics of the reservoir and affects the injection and production capacity of the gas storage. A set of experimental evaluation methods based on production characteristics is established by taking carbonate fracture-pore gas reservoir as the research object and combining with the production practice of gas reservoir; Carry out experimental research on the impact of effective stress change on injection production capacity, and quantitatively analyze the impact of internal characteristics of reservoir, multi cycle injection production and effective stress action time on injection production capacity. The results show, the experimental method established based on the actual production characteristics of the gas storage, thus realizing the experimental evaluation of the injection production capacity of the simulation multi cycle injection production of the gas storage; The change of effective stress makes the reservoir seepage characteristics worse and the reservoir space smaller, injection-production coefficient (Szc) is positively correlated with the internal characteristic value of the reservoir, the larger the internal characteristic value of the reservoir, the higher Szc, and the better the injection production capacity; The injection production capacity of the gas storage reservoir deteriorates with the increase of the injection production cycle, in the fourth injection production cycle, the injection production capacity of the gas storage reservoir changes from moderately strong to moderately weak; The damage of effective stress to the injection production capacity of gas reservoir mainly occurs in the initial stage of injection production, and the damage tends to be stable with the progress of injection production. It is concluded that in view of the problem that the effective stress change of carbonate fracture-pore type gas storage deteriorates the injection and production capacity of the reservoir, it is proposed to carry out reservoir reconstruction before the gas storage put into operation and expand the capacity of the gas storage after the completion of the third injection and production cycle, which can effectively offset the impact of the decline of the injection and production capacity of the gas storage.